Intent driven Internet of things - Jiaming ZHANG; Chungang YANG; Lei PANG; Jiandong LI (物联网学报)
Intent driven network (IDN) is an emerging network technology.With its advantages in intent translation,closed-loop verification and automate deployment,it has become another revolutionary network technology after software-defined network (SDN).Aiming at the problem of weak scalability,difficult data management and poor security performance in the current development of the Internet of things,the SDN-based intent driven Internet of things was proposed,and the north-south interface and other key technologies were introduced.Aiming at the consistency problem of multi-intention northbound interface,an intentional-conflict decomposition strategy was proposed,which is proved to be effective by simulation.